Economic growth and business cycles movements in Baltic and Western European countries - Zienius, Rimas (2021)
The present dissertation has as main goal analyze the differences of economic growth dynamics between Baltic countries and Western European countries. With this purpose data from OECD database was studied for the countries of Lithuania, Latvia, Estonia, Germany, France and United Kingdom. The analyzed period was the years from 1995 to 2017. The research consists of two main parts: analysis of the business cycle stages and the factors that affect GDP growth in Baltic and Western European countries. To identify business cycles stages we used the Hodrick-Prescott Filter and for the identifications and analysis of the variables affecting GDP growth we use GARCH and VAR models. The evidence shows different synchronization between Baltic and Western Europe countries business cycles. Baltic countries business cycles are more affected by local events, while Western European business cycles are affected by global economy growth. Moreover, it was find out those Baltic countries macroeconomic variables have higher instability compared with France, United Kingdom and Germany. Investment growth, share price growth and EU GDP growth have higher effect on GDP fluctuations in Baltic countries than in Western European countries. Using graphical analysis it was found that share price index decline, asset price decline and interest rate growth were signals for Baltic countries downturns period during 2008-2009 and 1998-1999.